Nitazoxanide in Patients Hospitalized With COVID-19 Pneumonia: A Multicentre, Randomized, Double-Blind, Placebo-Controlled Trial - Rocco, Patricia R. M.; Silva, Pedro L.; Cruz, Fernanda F.; Tierno, Paulo F. G. M. M.; Rabello, Eucir; Junior, Jéfiton Cordeiro; Haag, Firmino; de Ávila, Renata E.; da Silva, Joana D. G.; Mamede, Mariana M. S.; Buchele, Konrad S.; Barbosa, Luiz C. V.; et al. (Frontiers in Medicine, 2022)
Background: Nitazoxanide exerts antiviral activity in vitro and in vivo and anti-inflammatory effects, but its impact on patients hospitalized with COVID-19 pneumonia is uncertain. Methods: A multicentre, randomized, double-blind, placebo-controlled trial was conducted in 19 hospitals in Brazil. Hospitalized adult patients requiring supplemental oxygen, with COVID-19 symptoms and a chest computed tomography scan suggestive of viral pneumonia or positive RT-PCR test for COVID-19 were enrolled. Patients were randomized 1:1 to receive nitazoxanide (500 mg) or placebo, 3 times daily, for 5 days, and were followed for 14 days. The primary outcome was intensive care unit admission due to the need for invasive mechanical ventilation. Secondary outcomes included clinical improvement, hospital discharge, oxygen requirements, death, and adverse events within 14 days. Results: Of the 498 patients, 405 (202 in the nitazoxanide group and 203 in the placebo group) were included in the analyses. Admission to the intensive care unit did not differ between the groups (hazard ratio [95% confidence interval], 0.68 [0.38–1.20], p=0.179); death rates also did not differ. Nitazoxanide improved the clinical outcome (2.75 [2.21–3.43], p<0.0001), time to hospital discharge (1.37 [1.11–1.71], p=0.005), and reduced oxygen requirements (0.77 [0.64–0.94], p=0.011). C-reactive protein, D-dimer, and ferritin levels were lower in the nitazoxanide group than the placebo group on day 7. No serious adverse events were observed. Conclusions: Nitazoxanide, compared with placebo, did not prevent admission to the intensive care unit for patients hospitalized with COVID-19 pneumonia. Clinical Trial registration Brazilian Registry of Clinical Trials (REBEC) RBR88bs9x; ClinicalTrials.gov NCT04561219.